2013
DOI: 10.1002/jcph.113
|View full text |Cite
|
Sign up to set email alerts
|

Iron Chelation in the Treatment of Cancer: A New Role for Deferasirox?

Abstract: Iron plays a crucial role in a number of metabolic pathways including oxygen transport, DNA synthesis, and ATP generation. Although insufficient systemic iron can result in physical impairment, excess iron has also been implicated in a number of diseases including ischemic heart disease, diabetes, and cancer. Iron chelators are agents which bind iron and facilitate its excretion. Experimental iron chelators have demonstrated potent anti-neoplastic properties in a number of cancers in vitro. These agents have y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 70 publications
(106 reference statements)
0
56
1
2
Order By: Relevance
“…Having precise knowledge of the biosynthetic pathways of siderophores can be a true asset in biotechnology. Indeed, because of the strong metal chelating properties of these compounds and their importance in bacterial iron homeostasis, siderophores have many applications in either biomedical (Bedford et al ., ; Mislin and Schalk, ; Schalk and Mislin, ; Schalk, ) or bioremediation (Cornu et al ., ; Ferret et al ., ; Hazotte et al ., ) approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Having precise knowledge of the biosynthetic pathways of siderophores can be a true asset in biotechnology. Indeed, because of the strong metal chelating properties of these compounds and their importance in bacterial iron homeostasis, siderophores have many applications in either biomedical (Bedford et al ., ; Mislin and Schalk, ; Schalk and Mislin, ; Schalk, ) or bioremediation (Cornu et al ., ; Ferret et al ., ; Hazotte et al ., ) approaches.…”
Section: Discussionmentioning
confidence: 99%
“…A number of in vitro and in vivo studies have demonstrated that DFX has powerful antiproliferative effects [17]. To our knowledge, there have been no studies investigating the effects of DFX against pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, misregulation of this system would elicit detrimental effects on cells, such as the oncogenic effect of intracellularly retained free iron [1,2]. Deregulated systemic iron homeostasis contributes to cancer risk and progression [2,3].…”
Section: Introductionmentioning
confidence: 99%